2020
DOI: 10.1021/acsenergylett.0c01447
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence-Enabled Self-Reporting for Redox Flow Batteries

Abstract: Monitoring battery health is challenging. Self-reporting enables the rapid health assessment of redox flow batteries (RFBs) and provides insight into degradation mechanisms of electrochemically active molecules (redoxmers). Here we introduce fluorescence as an orthogonal property to probe this chemistry in situ. An established anolyte redoxmer, 2,1,3-benzothiadiazole, is rendered an efficient blue-green fluorophore through minimalistic derivatization. One of the derivatives is electrochemically reversible with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
2
16
0
Order By: Relevance
“…In a recent work, Robertson et al have identified that BzNSN molecules with λ abs values ranging from 350 to 400 nm exhibit fluorescence activity. 11 Our DFT calculations of a subset of 1400 BzNSNs also confirm that molecules with λ abs in this range possess the emission wavelength (λ em ) in the visible range (Figure S1). Since the computational evaluation of λ em is significantly more expensive than that of λ abs , we used the latter as an approximate screening indicator of the fluorescence activity.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…In a recent work, Robertson et al have identified that BzNSN molecules with λ abs values ranging from 350 to 400 nm exhibit fluorescence activity. 11 Our DFT calculations of a subset of 1400 BzNSNs also confirm that molecules with λ abs in this range possess the emission wavelength (λ em ) in the visible range (Figure S1). Since the computational evaluation of λ em is significantly more expensive than that of λ abs , we used the latter as an approximate screening indicator of the fluorescence activity.…”
Section: Resultssupporting
confidence: 58%
“…8−10 Recently, a BzNSN derivative, CH 3 -AcBzC 6 , was engineered with a π-extended acetamide group, 11 which enabled an orthogonal molecular property, namely fluorescence, to monitor the crossover of the active species and assess the state of health of the battery. 11 Hence, one promising strategy for designing anolyte redoxmers is to perform molecular engineering of the BzNSN scaffold using a wide range of functional groups to achieve the desired properties (e.g., using electron-withdrawing/-donating groups to tune the redox potential). However, high-throughput experimental synthesis and characterization are often a significant bottleneck, and high-fidelity computational methods provide a cost-efficient alternative to enable the design and discovery.…”
Section: Introductionmentioning
confidence: 99%
“…[64][65][66] Furthermore, derivatization of benzothiadiazole enabled self-reporting of battery health by fluorescence emission. 67 In this application we demonstrate our constrained optimization approach for the multi-objective design of retro-synthetically accessible redoxmer molecules. We utilize a previously reported dataset that comprises 1408 benzothiadiazole derivatives (Fig.…”
Section: Design Of Redox-active Materials For Flow Batteries With Syn...mentioning
confidence: 99%
“…The development of organic fluorophores has revolutionized in various fields such as electronics, 1-3 energy, 4 and medicine. [5][6][7] Organic fluorophores have better structure-property tunability, flexibility, and biocompatibility compared with inorganic light-emitting materials.…”
Section: Introductionmentioning
confidence: 99%